Crime by Proxy : Coercion and Altruism in Adolescent Shoplifting - Kivivuori, Janne (The British journal of criminology, 2007)
Historical criminology has described the underworld role of Fagin - an adult who forces, seduces or teaches minors to commit crimes for him. In contemporary debates, it is sometimes feared that adolescents cunningly evade criminal law by recruiting younger children to commit offences for them. The present article reports findings from three studies charting the prevalence and correlates of proxy crime among Finnish juvenile offenders. First, a preliminary study is briefly described, pinpointing shoplifting as a typical proxy crime. Second, the prevalence and correlates of proxy shoplifting are described by using a nationally representative community sample (N = 6,279). Of all 15-16-year-old respondents, 7.2 per cent had shoplifted for someone else. Third, a qualitative dataset including convicted property offenders (N = 12) is re-analysed from the point of view of how proxy crime may initiate serious criminal careers. The study suggests that while proxy crime may sometimes play a role at the onset of criminal careers, it is predominantly an inter-adolescent phenomenon, reflecting coercive and altruistic motives